Pengaruh Dukungan Keluarga dan Pasangan terhadap Resiliensi Ibu yang Memiliki Anak dengan Spektrum Autisme - Aisya Cinintya Saichu; Ratih Arruum Listiyandini (Universitas Katolik Soegijapranata, 2018)
Mothers of children with autism spectrum disorder experience more distress. Thus, mothers need psychological resilience, personal qualities that enable one to thrive in the face of adversity. In addition, during the nurturing period of their child, mother also need significant others which can give them social support. This study aims to determine how is the influence of family and partner support towards the resilience of mothers with autism child. The sample in this study was 103 mothers who have children with autism spectrum disorder. Participants were taken by purposive sampling method. The instrument used social support scale which created by reseacher to measure the level of perceived social support, and Indonesian adaptation of a resilience scale to measure resilience. The result of regression analysis showed that social support which contribute more to the resilience of mothers is informational support, both from family (16,2%) and partner (9,1%). Informational support defined as any kind of information or advice from others that can help the people who need in support. The results of this study implied about the value of information and advice from family and spouse for mothers. This kind of support will enable mothers to be more resilience on facing the difficulties that usually happened during the process of nurturing their autism child.